Crude Extract Preparation of Sea Grapes (Caulerpa racemosa) Using the Maceration Method - Ariya Abdul Gani; Anandita Ekasanti (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Sea grapes (Caulerpa racemosa) are a species of seaweed with considerable potential as a source of bioactive compounds; however, their utilization in Indonesia remains limited. This study aimed to describe the preparation process of crude extract from sea grapes using the maceration method and to determine its yield. The procedure involved drying the seaweed in a drying cabinet at 45 °C for 23 hours, grinding the dried material into simplicia powder using a chopper, macerating the powder with 96% ethanol at a ratio of 1:5 for three consecutive 24-hour periods, and evaporating the solvent with a rotary evaporator at 40 °C. The obtained extract was further concentrated using a water bath until a paste form was achieved. From 3 kg of fresh material, 100 g of dried simplicia was produced, yielding 5.595 g of crude extract with a yield value of 5.595%. The maceration method was selected due to its efficiency, simplicity, and minimal requirement for specialized equipment. Ethanol 96% was chosen as the solvent because of its ability to dissolve both polar and non-polar active compounds and its safety for consumable products